Students' Preference of Language Learning Style in English Classroom: A Survey at SMP Gembala Baik Bilingual Class Pontianak - Paramita, Paulina Erawati (Indo Publishing, 2026)
This study investigated the preferred language learning styles of students in a bilingual junior high school setting and examined gender-based differences in these preferences. A quantitative survey design was employed, utilizing the VAK (Visual, Auditory, Kinesthetic) Learning Styles Self-Assessment Questionnaire originally developed by Fleming and Mills (1992). The sample comprised 100 students from SMP Gembala Baik Bilingual Class Pontianak, selected through coincidental sampling across grades VII, VIII, and IX. Data were analyzed using descriptive statistics to determine the distribution of learning style preferences and to compare patterns between male and female students. The findings revealed that visual learning was the most dominant preference overall (41%), followed by auditory (33%) and kinesthetic (26%). Gender-based analysis showed distinct patterns: male students predominantly preferred kinesthetic learning (44.8%), while female students demonstrated strongest preference for visual learning (50.0%). These results align with recent Indonesian studies on gender and learning styles and contribute to the growing body of evidence supporting differentiated instruction in bilingual educational contexts. The study concludes that recognizing diverse learning styles enables teachers to implement multimodal teaching strategies that accommodate all learners, ultimately enhancing English language proficiency in junior high school